Prevention of Dental Caries in Pregnant Women and Stunting Prevention Through Interactive Edcation - Bedjo Santoso; Jeffri Ardiyanto; Marsum; Manzilina Hani Baity Jannaty; Rose Asni Lathifah; Lanny Hapsari Winnursita (⁠International Journal of Asia Pacific Community Service, 2026)
Poor dental and oral health status of pregnant women has an impact on the development of early childhood caries which can result in many consequences for the child's health in the future. Preventing dental infections during pregnancy requires pregnant women to receive dental and oral health education as well as self-care behavior education. The purpose of this community service is to increase the knowledge of pregnant women in preventing dental caries. The implementation of community service through dental and oral health education through smart catalogs and assistance in brushing teeth practices in pregnant women is able to increase knowledge, attitudes and actions to maintain dental health and reduce the index debris score in pregnant women.